CXC chemokine ligand 4 induces a unique transcriptome in monocyte-derived macrophages - Gleißner, Christian A.; Shaked, Iftach; Little, Kristina M.; Ley, Klaus (The journal of immunology, 2010)
In atherosclerotic arteries, blood monocytes differentiate to macrophages in the presence of growth factors, such as macrophage colony-stimulation factor (M-CSF), and chemokines, such as platelet factor 4 (CXCL4). To compare the gene expression signature of CXCL4-induced macrophages with M-CSF-induced macrophages or macrophages polarized with IFN-γ/LPS (M1) or IL-4 (M2), we cultured primary human peripheral blood monocytes for 6 d. mRNA expression was measured by Affymetrix gene chips, and differences were analyzed by local pooled error test, profile of complex functionality, and gene set enrichment analysis. Three hundred seventy-five genes were differentially expressed between M-CSF- and CXCL4-induced macrophages; 206 of them overexpressed in CXCL4 macrophages coding for genes implicated in the inflammatory/immune response, Ag processing and presentation, and lipid metabolism. CXCL4-induced macrophages overexpressed some M1 and M2 genes and the corresponding cytokines at the protein level; however, their transcriptome clustered with neither M1 nor M2 transcriptomes. They almost completely lost the ability to phagocytose zymosan beads. Genes linked to atherosclerosis were not consistently upregulated or downregulated. Scavenger receptors showed lower and cholesterol efflux transporters showed higher expression in CXCL4- than M-CSF-induced macrophages, resulting in lower low-density lipoprotein content. We conclude that CXCL4 induces a unique macrophage transcriptome distinct from known macrophage types, defining a new macrophage differentiation that we propose to call M4.